2017
DOI: 10.1097/mpg.0000000000001554
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Follow‐up Study of Pediatric Orofacial Granulomatosis Patients

Abstract: Long-term follow-up of pediatric-onset patients with OFG shows good prognosis. Patients with OFG do not seem to have otorhinolaryngological comorbidity. Anti-S cerevisiae antibody A may serve as a factor to indicate the possible presence of underlying CD in patients with OFG, but further studies are requested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
1
12
1
1
Order By: Relevance
“…One-quarter of the patients reported suffering from angular cheilitis. In patients with OFG, angular cheilitis was found in half of the patients, and in patients with paediatric CD, it was the most frequently seen oral lesion, present in 15% of the patients [6,17]. However, angular cheilitis is not specific to CD or OFG, and it is also observed in otherwise healthy individuals.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…One-quarter of the patients reported suffering from angular cheilitis. In patients with OFG, angular cheilitis was found in half of the patients, and in patients with paediatric CD, it was the most frequently seen oral lesion, present in 15% of the patients [6,17]. However, angular cheilitis is not specific to CD or OFG, and it is also observed in otherwise healthy individuals.…”
Section: Discussionmentioning
confidence: 94%
“…In an earlier study, we investigated the connection between OFG and CD, and explored the factors leading to bowel disease in patients presenting with orofacial symptoms. We found that 72% of patients with paediatric-onset OFG developed a symptomatic bowel disease, namely CD, during a median of 3.1 years follow-up [6]. However, whether patients with MRS develop a symptomatic bowel disease in long-term follow-up has not been determined.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Both OFG and CD are intermittent with steady and acute phases. In OFG and oral CD, a predominant clinical finding is lip swelling followed by intra-oral features like hyperplastic gingivitis and cobblestoning, oral ulcers, and mucosal tags (Pittock et al 2001;Harty et al 2005;Al Johani et al 2010;Campbell et al 2011a;McCartan et al 2011;Haaramo et al 2017). However, it is reported that the overall discomfort, as well as the duration of symptoms and problems with appearance, are more severe in OFG than in oral CD patients (Gale et al 2015;Miest et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Being a rare disease, no epidemiological data on OFG exist. Patient characteristics are mainly based on cohorts and case series (Mignogna et al 2003 ; Al Johani et al 2009 ; Saalman et al 2009 ; McCartan et al 2011 ; Gale et al 2015 ; Haaramo et al 2017 ). However, there seems to be an increase in the frequency of OFG in children and young adults in the Western world (Leao et al 2004 ; Saalman et al 2009 ; Campbell et al 2011a ; Lazzerini et al 2014 ) and a prevalence as high as 0.8% has been suggested in the Celtic population (McCartan et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%